Unlocking prosperity: economic potential of Cordyceps mushroom cultivation as a promising agri-enterprise in India: Economics of Cordyceps cultivation - Bijla, Shweta; Kumar, Satish; Sharma, Ved Parkash (Mushroom Research, 2024)
Modern agribusiness in India is beholding a major shift, driven by the need to address nutritional security, mitigate the risks of traditional agriculture, and provide viable opportunities for resource-constrained farmers. Cordyceps mushroom, also known as “soft gold”, renowned for its exceptional medicinal and nutraceutical properties, offers immense potential as a lucrative enterprise in the country. It is important to analyse the economics of Cordyceps mushroom to boost its adoption among next-gen mushroom growers. Present paper helps in effective financial planning and provides acumens into the minimum viable scale required to establish a successful Cordyceps mushroom enterprise. The return over variable cost (ROVC) for small, medium, and large growers was Rs. 12000, Rs. 16000, and Rs. 22000 per Kg per crop cycle of Cordyceps mushroom. The BC Ratio is viable only for medium and larger units opposed to small units. The Break Even Point (BEP) for small, medium, and large units above which they should produce to earn positive returns were 7 kg, 15 Kg, and 12 Kg per cycle, respectively.